Study on the pore structure of eco-regenerated mortar using corn cob based on nuclear magnetic resonance - Zhou Zhang; Chaolin Wang; Yu Zhao; Kun Zhang; Mingxuan Shen (Developments in the Built Environment)
This study aims to investigate the influence of corn cob particles on pore structure of mortar. By using NMR technology, the pore parameters of fast-hardening sulfoaluminate cement mortar (SAC) and ordinary Portland cement mortar (PO) were measured and compared. The influence of corncob particles on the mechanical properties of eco-mortar was evaluated by uniaxial compression test. The results indicate that medium and large pores of both SAC and PO increases with corn cob particle, as well as the porosity. The fractal dimensions of harmful and multiple harmful pores are negatively correlated with the volume fraction of corn cob particles. The addition of corn cob particles reduced the overall fractal dimension of the mortar and decreased the complexity of internal pores. The probability density function of grayscale values transitions from being “thin and tall” to “short and wide”, with an increasing proportion of high grayscale values. This leads to an increase in the proportion of large pores within the mortar, resulting in a continuous deterioration of pore structure. The addition of corn cob particles greatly reduces the strength of SAC and PO, but the peak stress of SAC is higher than that of PO. When corn cob particle content is 30 wt% and 50 wt%, the peak stress of SAC is increased by 23.37% and 14.25%, respectively, compared with the peak stress of PO.